Establishment of Epiphytic Bromeliads in Successional Tropical Premontane Forests in Costa Rica - Cascante Marín, Alfredo (2008)
Plant community composition is the combined result of species‐specific competitive abilities and the availability of propagules. For epiphytic plants, current hypotheses consider that dispersal‐related factors are most important. By controlling seed dispersal constraints, we experimentally examined whether the community composition of epiphytic bromeliads in a tropical premontane area is determined during early phases of seedling recruitment. Also, we tested whether establishment success was related to eco‐physiological traits of the species. A total of 7200 seeds were artificially affixed on several host trees in two secondary forest patches and in a mature forest stand. Four bromeliad species with differing physiological characteristics (CAM, C3‐CAM, and C3) and habitat preference (secondary vs. primary forest) were selected. We found that differences in seed germination probability among habitats and species were not likely to influence community assembly. After 2 yr, seedling survival and plant development were relatively higher in the early‐successional forest. Seedling establishment success was not associated with specific physiological and morphological adaptations or habitat preference of the studied species. Our results were not consistent with the described community composition and rates of population recruitment of the studied species in the same successional habitats. The results support the hypothesis that chance and historic events related to seed dispersal have an important influence on community assembly of epiphytic plants. In addition, differences in growth rates and reproductive turnover among species are expected to influence the relative abundance and recruitment rates in a particular habitat.